Generalized Convexity, Generalized Monotonicity and Applications Proceedings of the 7th International Symposium on Generalized Convexity and Generalized Monotonicity - Eberhard, Andrew; Hadjisavvas, Nicolas; Luc, D.T (Nonconvex Optimization and Its Applications, 2005)
This volume contains a collection of refereed articles on generalized convexity and generalized monotonicity. The first part of the book contains invited papers by leading experts (J.M. Borwein, R.E. Burkard, B.S. Mordukhovich and H. Tuy) with applications of (generalized) convexity to such diverse fields as algebraic dynamics of the Gamma function values, discrete optimization, Lipschitzian stability of parametric constraint systems, and monotonicity of functions. The second part contains contributions presenting the latest developments in generalized convexity and generalized monotonicity: its connections with discrete and with continuous optimization, multiobjective optimization, fractional programming, nonsmooth Aanalysis, variational inequalities, and its applications to concrete problems such as finding equilibrium prices in mathematical economics, or hydrothermal scheduling. Audience This volume is suitable for faculty, graduate students, and researchers in mathematical programming, operations research, convex analysis, nonsmooth analysis, game theory and mathematical economics.